Molecular characterization of homozygous hereditary factor I deficiency - BARACHO, G V (Blackwell Publishing Inc, 2003)
We have studied the molecular basis of factor I (fI) deficiency in two Brazilian sisters from a consanguineous family. By reverse transcription-polymerase chain reaction we observed that all fI cDNA amplified products from one sister had the same size as those of normal cDNA, however, they were significantly less intense. Sequencing analysis of subcloned cDNA revealed a dinucleotide insertion (AT) between positions 1204 and 1205 in the 11th exon that creates a stop codon 13 bp downstream of the insertion site. Genomic DNA sequencing and heteroduplex analysis confirmed that both probands are homozygous for this mutation, whereas their parents are heterozygous. The stop codon and the diminished amounts of fI cDNA could indicate increased fI mRNA instability, perhaps due to a mechanism of nonsense-mediated decay. This hypothesis is consistent with our observation that treatment with the translation inhibitor cycloheximide stabilized fI mRNA expression in proband's fibroblasts.